Somatotropin Effective Antisera Production In Forty Days (Applied Biological Research, 2013)
Polyclonal antisera were raised against bovine somatotropin (ST) in rabbits  and high titer achieved in less than 40 days after primary immunization.  Protocol was developed with slight modification in method of Hu (2002) for  antisera production and booster injection given on 28th and 37th day. The  serum for antibody titer was collected on 35th and 42nd day. The antisera  procured were effective in Western blotting and for purification of ST using  affinity column chromatography.
Keywords: Affinity column; polyclonal antisera; protein purification; somatotropin